Peran Penyuluh Kantor Urusan Agama dalam Meningkatkan Baca Tulis Al-Qur’an (BTQ) Mualaf di Kecamatan Ampel Kabupaten Boyolali - Shodiq, Nur; Kharis, Ahmad; Mustolich, Muhammad (Tadbir: Jurnal Manajemen Dakwah, 2025)
This research aims to (1) To find out the role of sub-district instructors in improving the reading and writing of the Qur'an for converts to Islam in Ampel sub-district (2) To find out the procedures for instructors in teaching reading and writing of the Qur'an to converts in Ampel district. This type of research is a type of field research and is a qualitative description. Data sources in this research include primary sources and secondary sources. This data collection was carried out by conducting interviews, observation and documentation. The results of this research show that: 1) the process of guidance for converts to Islam is carried out once a week, where guidance is carried out in stages in carrying out guidance on reading the Al-Qur'an using the Iqra method. 2). Guidance carried out using the Iqra method is carried out by studying the Al-Qur'an from volume I to volume VI periodically or gradually, starting from the introduction of sounds, pronunciation of sounds, the names of hijaiyah hufuf and how to read to the listening process. with tadarus.